IMPACT OF THE FURRING ON FUEL CONSUMPTION OF STEAM-GENERATING INSTALLATIONS OF THE OIL GAS TECHNOLOGICAL TRANSPORT - Kozak, Fedir; Bogatchuk, Ivan; Prunko, Igor; Bogatchuk, Mykhailo (Scientific Works of Vinnytsia National Technical University, 2018)
The paper considers the problem of the impact of the furring on the heating elements of mobile steam generating installation (SGI), widely used in oil and gas industry for the dewaxing of wells, pipe-lines, oil and gas as well as other equipment by the saturated steam of high and low pressure, and for other domestic and industrial needs. As steam-generating installations operate in field conditions at large distance from the main bases of their location (storage and registration), this leads to the forced consumption of physically and chemically untreated raw water. As a rule, this is subsurface natural water, water from rivers, lakes, pond, etc. Operation of steam-generating installations on the untreated water results in formation of the scale , which causes excess fuel consumption and failure of the steam generator boiler as a result of the coil burnout. However, even in the course of operation on the treated feed water the scale is formed on the walls of the coil, it decreases the operation efficiency and requires periodic descaling by means of acid treatment after 48 – 72 hours of operation. Operators often create the conditions for the creation of the thick layers of the scale and excess fuel consumption for the obtaining of the needed amount of steam, as compared with the data, specified by the regulatory documents on the installations operation. The paper contains the analysis of the impact of the scale layer thickness on thermal losses of the steam-generating installation boiler and the impact of the fur layer on the excess fuel consumption of the mobile steam-generating installation. Mathematical dependence of the excess fuel consumption on scale layer thickness is obtained. It was shown that the emergence of the scale causes not only economic but also ecological problems. In order to eliminate the negative impact of the scale on steam-generating installation operation the construction of the cleaning element was suggested. Application of the suggested device will enable to save up to 10.5 % of the fuel (approximately 121.5 kg/hr.). Taking into account the retail cost of the diesel fuel 27 UAH./l it is possible to achieve savings of 3280.5 UAH/ hour of the operation of one steam-generating installation. Thus, problem, considered in the paper is rather important for the enterprises of oil and gas industry.